Assessing the Impacts of Floods on Baraki Barak District of Logar Province - Peroz, Sharifullah; Sahak, Kawon; Mujeeb, Mujeebullah (Journal of Natural Sciences – Kabul University, 2024)
A flood is a natural phenomenon that occurs as a result of heavy and intense rainfall, snowmelt or a combination of both of them. And put some economic, social, environmental and health problems. The aim of this research is to assess the impact of floods on baraki- barak districts.the method of research is field based and the questionnaire is a set of 14 standard questions. Data was collected from 270 residents of the districts and analyzed through using Excel. Result shows that this district is the second vulnerable district after pul-e-alam to floods. Cropland, residential houses, livestock, residence and small connecting roads are more vulnerable to floods. According to the result of this research it is suggested that the government should prevent the intervention of people in the Loger river basin, prevent deforestation and establish flood warming and forecast systems.